(untitled) (Journal of Educational Sciences, 2022)
Massive open online courses (MOOCs) provide excellent learning opportunities as a modern distance learning technology. Discussion forums are the most active pedagogical component of massive open online courses. Forums are characterized by a number of opportunities, such as the creation of a global community of learners, active exchange of ideas and interaction, collaborative problem solving, building knowledge and development of digital skills. The purpose of the research is to identify characteristics of discussion forums and opportunities of applying them in the educational process. It will be effective in solving didactic problems if we use modern distance learning technologies in the process of virtual learning, such as discussion forums in massive open online courses for an active interaction, sharing and building knowledge with a broad audience. As a result of the research, based on the analysis of the international review of literature, forum peculiarities and their application in massive open online courses are theoretically summarized. In addition, a brief survey is conducted to examine the experiences and attitudes of 3rd year students’ participation in educational discussion forums at Abai Kazakh National Pedagogical University. A total of 87 students participated in the study. As a result of the study, it was found that students have little experience related to massive open online courses and discussion forums but they express high motivation to participate them. Key words: Massive open online courses (MOOCs), connectivism, discussion forums